Method of manufacturing metal-clad laminate

JP2025036137AActive Publication Date: 2025-03-14合同会社ニスティ +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024115371
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-04
Filing Date
2024-07-19
Publication Date
2025-03-14
Estimated Expiration
2044-07-19

AI Technical Summary

Benefits of technology

【0013】 本開示の金属張積層体の製造方法によれば、異方性が改善されたLCPラミネートフィルムを有する金属張積層体を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036137000001_ABST
    Figure 2025036137000001_ABST
Patent Text Reader

Abstract

To provide a metal-clad laminate and a method of manufacturing the same capable of improving anisotropy of an LCP film, and joining a metallic foil onto an LCP film with high strength.SOLUTION: A method of manufacturing a metal-clad laminate comprises: a laminating step of laminating lamination precursors of a first liquid crystal polymer film, a second liquid crystal polymer film, and a first metal foil so that the liquid crystal polymer films directly face each other; a heating step of heating the lamination precursors at a temperature 15 to 45°C higher than a higher first melting point between the melting points of the first liquid crystal polymer film and the second liquid crystal polymer film for 1 to 60 minutes under an environment of a vacuum level of 200 hPa or less; and a pressurizing step of starting cooling after completion of the heating step, and pressurizing the lamination precursors toward a lamination direction with a first pressure of 0.5 to 5 MPa. In the laminating step, the first liquid crystal polymer film and the second liquid crystal polymer film are laminated so that a stretching direction of the first liquid crystal polymer film and a stretching direction of the second liquid crystal polymer film make an angle of 80 to 100°.SELECTED DRAWING: Figure 8
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a metal clad laminate in which a liquid crystal polymer film and a metal foil are laminated, and a method for manufacturing the metal clad laminate. [Background technology]

[0002] Demand for equipment for the fifth generation communication (5G) system is increasing. As a result, attention is being paid to thermoplastic liquid crystal polymer (LCP; Liquid Crystal Polymer) films as a material with low transmission loss at high frequencies. In the following, liquid crystal polymer may be abbreviated as "LCP."

[0003] LCP is a polymer in which molecular chains are aligned in one direction in a molten state to exhibit liquid crystallinity. The molecular chains are oriented along the melt extrusion direction (MD) when producing an LCP film. Due to this molecular chain orientation, the tensile strength is lower in the MD than in the perpendicular direction (TD) and the linear expansion coefficient is higher, resulting in problems of anisotropy. For example, Patent Document 1 describes a method for producing a multiaxially oriented laminate in which multiple sheets of thermotropic liquid crystal polymers substantially oriented in one direction are thermally bonded together by changing their orientation.

[0004] For example, Patent Document 2 describes a method for producing a metal-clad laminate of a thermoplastic liquid crystal polymer film and a metal sheet by roll-to-roll processing. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 58-31718 [Patent Document 2] International Publication No. 2017 / 154811 Summary of the Invention [Problem to be solved by the invention]

[0006] The following analysis is provided in light of the present disclosure.

[0007] In the method for producing a multiaxially oriented laminate described in Patent Document 1, two LCP films are bonded under atmospheric pressure. However, heat bonding under atmospheric pressure does not sufficiently improve anisotropy. In addition, voids generated in the obtained LCP laminate film significantly reduce the resin strength of the LCP laminate film. In addition, Patent Document 1 does not describe or suggest bonding a metal foil to a multiaxially oriented laminate, or a metal clad laminate to which a metal foil is bonded.

[0008] In the method for producing a metal-clad laminate described in Patent Document 2, the anisotropy of the LCP film cannot be improved. If the anisotropy of the LCP film is improved before the production of the metal-clad laminate in Patent Document 2, an additional process is required, resulting in a method for producing a metal-clad laminate with low production efficiency. In addition, the metal-clad laminate produced by the method for producing a metal-clad laminate described in Patent Document 2 does not include a pressurizing process, so the peel strength between the metal foil and the LCP film cannot be increased. Furthermore, in the roll-to-roll method of Patent Document 2, since the pressurizing process is not performed, the produced metal-clad laminate is warped by more than 3 mm, which causes a problem in that the transportation of the printed circuit board in the solder reflow process is hindered.

[0009] Therefore, it is desired to provide a method for producing a metal clad laminate that can improve the anisotropy of the LCP film and can bond a metal foil to the LCP film with high strength. [Means for solving the problem]

[0010] According to a first aspect of the present invention, there is provided a method for producing a metal-clad laminate, comprising: a lamination step of laminating a laminate precursor of a first liquid crystal polymer film, a second liquid crystal polymer film, and a first metal foil so that a surface of the first liquid crystal polymer film and a surface of the second liquid crystal polymer film directly face each other; a heating step of heating the laminate precursor for 1 minute to 60 minutes in an environment with a degree of vacuum of 200 hPa or less at a temperature 15°C to 45°C higher than a first melting point, which is the higher of the melting points of the first liquid crystal polymer film and the second liquid crystal polymer film; and a pressurizing step of starting cooling after the heating step and pressurizing the laminate precursor in the lamination direction at a first pressure of 0.5 MPa to 5 MPa. In the lamination step, the first liquid crystal polymer film and the second liquid crystal polymer film are laminated so that the stretching direction of the first liquid crystal polymer film and the stretching direction of the second liquid crystal polymer film form an angle of 80° to 100°.

[0011] According to a second aspect of the present invention, there is provided a metal clad laminate having a second liquid crystal polymer layer, a first liquid crystal polymer layer, and a first metal layer in this order, in which the peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m, the orientation (MD / TD ratio) of the laminate film consisting of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, the resin strength of the laminate film is 100 MPa or more, and the amount of warping is 3 mm or less.

[0012] According to a third aspect of the present invention, there is provided a metal clad laminate having a second metal layer, a second liquid crystal polymer layer, a first liquid crystal polymer layer, and a first metal layer, in that order, wherein the peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m, the peel strength between the second liquid crystal polymer layer and the second metal layer is 0.9 kN / m to 2.5 kN / m, the orientation (MD / TD ratio) of the laminate film consisting of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, the resin strength of the laminate film is 100 MPa or more, and the warpage is 3 mm or less. Effect of the Invention

[0013] According to the manufacturing method of a metal clad laminate of the present disclosure, it is possible to manufacture a metal clad laminate having an LCP laminate film with improved anisotropy.

[0014] According to the method for producing a metal clad laminate of the present disclosure, the step of improving the anisotropy and the step of bonding a metal foil to an LCP laminate film can be carried out simultaneously.

[0015] According to the manufacturing method of the metal clad laminate of the present disclosure, it is possible to manufacture a metal clad laminate having high bonding strength and high resin strength as well as high dimensional accuracy.

[0016] According to the manufacturing method for a metal clad laminate disclosed herein, by using a laminate precursor having two or more first laminate units each having a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil laminated in that order, and a thin planar heater disposed between adjacent first laminate units, it is possible to achieve a significant improvement in productivity without unevenness in the heating temperature.

[0017] According to the manufacturing method for a metal clad laminate of the present disclosure, the laminate precursor has two or more second laminate units each having a second metal foil, a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil laminated in that order, and by using a laminate precursor in which a thin planar heater is disposed between adjacent second laminate units, it is possible to achieve a significant improvement in productivity without causing unevenness in the heating temperature.

[0018] The metal clad laminate of the present disclosure is of high quality having high bonding strength and resin strength, as well as high dimensional accuracy, little generation of voids, and little warping. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a flow chart showing an example of a process flow in a manufacturing method for a metal clad laminate according to the first embodiment of the present disclosure. [Diagram 2]FIG. 2 is a schematic side view showing an example of a laminate precursor. [Diagram 3] FIG. 3 is a schematic side view showing another example of the laminate precursor. [Figure 4] FIG. 4 is a schematic view for explaining the method for manufacturing the metal clad laminate according to the first embodiment. [Diagram 5] FIG. 5 is a schematic diagram for illustrating the method for manufacturing the metal clad laminate according to the first embodiment. [Figure 6] FIG. 6 is a schematic diagram showing an example of a laminate precursor having a multi-layer structure. [Figure 7] FIG. 7 is a schematic diagram showing another example of a laminate precursor having a multi-layer structure. [Figure 8] FIG. 8 is a schematic diagram showing an example of a metal clad laminate of the present disclosure. [Figure 9] FIG. 9 is a schematic diagram showing another example of the metal clad laminate of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Preferred embodiments of each of the above aspects are described below.

[0021] According to a preferred embodiment of the first aspect, the method includes an annealing step of reducing the first pressure to a second pressure that is 1 / 2 to 1 / 20 of the first pressure within a temperature range of a first glass transition temperature to a first melting point, which is the lower of the glass transition temperatures of the first liquid crystal polymer film and the second liquid crystal polymer film, and maintaining the temperature range and second pressure for 5 to 60 minutes.

[0022] According to a preferred embodiment of the first aspect, the melting point of the first liquid crystal polymer film and the melting point of the second liquid crystal polymer film are each within a range of 270°C to 340°C.

[0023] According to a preferred embodiment of the first aspect, the first liquid crystal polymer film and the second liquid crystal polymer film have the same material.

[0024] According to a preferred embodiment of the first aspect, the ten-point height deviation of the surface of the first metal foil facing the first liquid crystal polymer film is 1.5 μm or less.

[0025] According to a preferred embodiment of the first aspect, the first metal foil is an electrolytic copper foil or a rolled copper foil having a thickness of 3 μm to 40 μm.

[0026] According to a preferred mode of the above first aspect, in the produced metal clad laminate, the peel strength between the first liquid crystal polymer film and the first metal foil is 0.9 kN / m to 2.5 kN / m.

[0027] According to a preferred embodiment of the first aspect, in the laminating step, the laminate precursor is prepared in a mold. In the pressing step, the laminate precursor is pressed while being shaped in the mold.

[0028] According to a preferred embodiment of the first aspect, the laminate precursor further includes a second metal foil. In the lamination step, the first liquid crystal polymer film and the first metal foil are disposed so that their surfaces directly face each other. The second liquid crystal polymer film and the second metal foil are disposed so that their surfaces directly face each other.

[0029] According to a preferred embodiment of the first aspect, the second metal foil is an electrolytic copper foil or rolled copper foil having a thickness of 3 μm to 40 μm. The ten-point average roughness of the surface of the second metal foil facing the second liquid crystal polymer film is 1.5 μm or less.

[0030] According to a preferred mode of the above first aspect, in the produced metal clad laminate, the peel strength between the second liquid crystal polymer film and the second metal foil is 0.9 kN / m to 2.5 kN / m.

[0031] According to a preferred embodiment of the first aspect, the laminate precursor has two or more first laminate units each having a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil laminated in this order, and a thin planar heater is disposed between adjacent first laminate units.

[0032] According to a preferred embodiment of the first aspect, the laminate precursor has two or more second laminate units each having a second metal foil, a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil laminated in this order, and a thin sheet heater is disposed between adjacent second laminate units.

[0033] According to a preferred embodiment of the first aspect, the thin sheet heater is capable of heating to 300° C. or higher.

[0034] According to the preferred embodiments of the second and third aspects, the area of ​​the laminate film is 10 cm 2 The average number of voids with a diameter of 0.5 mm or less per unit area is 5 or less.

[0035] According to a preferred embodiment of the second and third aspects, the laminate film has a linear expansion coefficient ratio in the plane direction (MD / TD) of 1.2 or less and a linear expansion coefficient in the thickness direction (z direction) of 45 ppm or less.

[0036] According to a preferred embodiment of the second and third aspects, the first metal layer and the second metal layer are electrolytic copper layers or rolled copper layers having a thickness of 3 μm to 40 μm.

[0037] According to a preferred embodiment of the second and third aspects, the metal clad laminate is used for a flexible printed circuit board or a rigid printed circuit board.

[0038] A method for manufacturing a metal clad laminate according to a first embodiment of the present disclosure will be described. Fig. 1 is a flow chart showing an example of a process flow in the method for manufacturing a metal clad laminate according to the first embodiment of the present disclosure. Hereinafter, the process flow in the method for manufacturing a metal clad laminate of the present invention will be described.

[0039] In step S11 (lamination step), the first liquid crystal polymer film and the second liquid crystal polymer film in the laminate precursor are laminated so that their surfaces directly face each other, and then the process proceeds to S12.

[0040] In step S12 (heating step), the material is heated in an environment with a degree of vacuum of 200 hPa or less at a temperature 15° C. to 45° C. higher than the first melting point for 1 to 60 minutes, and then the process proceeds to S13.

[0041] In step S13 (pressurizing step), after the heating step is completed, cooling is started, and the laminated precursor is pressurized in the lamination direction at a first pressure of 0.5 MPa to 5 MPa, and then the process proceeds to S14.

[0042] In step S14 (annealing process), the first pressure is reduced to a second pressure within the temperature range of the first glass transition temperature to the first melting point, and the temperature range and second pressure are maintained for 5 to 60 minutes, after which the process is terminated.

[0043] As described above, according to the manufacturing method of the metal clad laminate of the first embodiment of the present disclosure, a metal clad laminate having high bonding strength and high resin strength as well as high dimensional accuracy can be manufactured.

[0044] The metal clad laminate in the present disclosure refers to a laminate of an LCP laminate film and a metal foil. The LCP laminate film in the present disclosure is a film in which at least two LCP films are laminated and melt-integrated. In the LCP laminate film, the number of LCP films laminated can be, for example, two, three, or four. In the metal clad laminate in the present disclosure, a metal foil is laminated on at least one surface of the LCP laminate film. A metal foil may be laminated on both surfaces of the LCP laminate film. The metal clad laminate in the present disclosure may be a multilayer structure in which an LCP laminate film and a metal foil are alternately laminated.

[0045] In the metal clad laminate of the present disclosure, the LCP films that are directly overlapped are bonded (fused) to each other, and the LCP film and metal foil that are directly overlapped are bonded with high strength.

[0046] A schematic side view of the laminate precursor according to the first embodiment is shown in Fig. 2. The laminate precursor 10 in the present disclosure refers to a laminate of at least two LCP films 1 and 2 and at least one metal foil 3 prior to the completion of the production of a metal clad laminate.

[0047] The laminate precursor 10 is produced by laminating a first LCP film 1, a second LCP film 2, and a first metal foil 3 so that the surface of the first LCP film 1 and the surface of the second LCP film 2 directly face each other.

[0048] The first LCP film 1 and the second LCP film 2 are laminated so that the stretching direction (extrusion direction) of the first LCP film 1 during production and the stretching direction (extrusion direction) of the second LCP film 2 during production form an angle of 80° to 100°. This makes it possible to reduce the anisotropy of the orientation of the LCP laminate film. The angle formed by the first LCP film 1 and the second LCP film 2 is preferably 85° to 95°, and most preferably 90°.

[0049] A schematic side view of the laminate precursor according to the second embodiment is shown in FIG. 3. The laminate precursor 20 may further include a second metal foil 4 as shown in FIG. 3. In the lamination step, the first LCP film 1 and the first metal foil 3 may be arranged so that their surfaces directly face each other. The second LCP film 2 and the second metal foil 4 may be arranged so that their surfaces directly face each other. This allows the laminate precursor 20 to have a structure in which the first LCP film 1 and the second LCP film 2 are sandwiched between the first metal foil 3 and the second metal foil 4.

[0050] The laminate precursors 10 and 20 may further include an LCP film (not shown) other than the first LCP film 1 and the second LCP film 2. The laminate precursors 10 and 20 may further include a metal foil (not shown) other than the first metal foil 3 and the second metal foil 4.

[0051] The laminate precursors 10, 20 are preferably formed between mirror plates covering the LCP film surface and the metal foil surface.

[0052] The LCP applicable to the manufacturing method of the metal clad laminate of the present disclosure is not particularly limited as long as it has thermoplasticity. The LCP is preferably one that forms an anisotropic molten body at a temperature of 400° C. or less. The first LCP and the second LCP may be made of the same material or different materials. The first LCP and the second LCP are preferably made of the same material.

[0053] A known polymer can be used as the LCP in the manufacturing method of the metal clad laminate of the present disclosure. The LCP preferably contains a p-hydroxybenzoic acid component. In addition to the p-hydroxybenzoic acid component, the LCP may contain at least one component selected from the group consisting of a 4,4'-dihydroxybiphenyl (biphenol) component, a terephthalic acid component, an isophthalic acid component, a 6-hydroxy-2-naphthoic acid component, and an ethylene terephthalate component.

[0054] The LCP may be, for example, a polyester containing a 6-hydroxy-2-naphthoic acid component and a p-hydroxybenzoic acid component. The 6-hydroxy-2-naphthoic acid component may be, for example, 15 mol% to 40 mol% based on the total amount of the monomer components of the LCP. The p-hydroxybenzoic acid component may be, for example, 60 mol% to 85 mol% based on the total amount of the monomer components of the LCP.

[0055] The LCP may be, for example, a polyester containing a 6-hydroxy-2-naphthoic acid component, a terephthalic acid component, and a p-hydroxybenzoic acid component. The 6-hydroxy-2-naphthoic acid component may be, for example, 15 mol% to 40 mol% based on the total amount of the monomer components of the LCP. The terephthalic acid component may be, for example, 1 to 5 mol% based on the total amount of the monomer components of the LCP. The p-hydroxybenzoic acid component may be, for example, 65 mol% to 84 mol% based on the total amount of the monomer components of the LCP.

[0056] The LCP may be, for example, a polyester containing a 4,4'-dihydroxybiphenyl component, a 6-hydroxy-2-naphthoic acid component, a terephthalic acid component, and a p-hydroxybenzoic acid component. The 4,4'-dihydroxybiphenyl component may be, for example, 5 mol% to 25 mol% based on the total amount of the monomer components of the LCP. The 6-hydroxy-2-naphthoic acid component may be, for example, 5 mol% to 15 mol% based on the total amount of the monomer components of the LCP. The terephthalic acid component may be, for example, 5 mol% to 15 mol% based on the total amount of the monomer components of the LCP. The p-hydroxybenzoic acid component may be, for example, 50 mol% to 80 mol% based on the total amount of the monomer components of the LCP.

[0057] LCP can be produced by a known method, and a commercially available LCP can be used.

[0058] The melting point of each LCP is preferably within the range of 270° C. to 340° C. The melting point can be measured, for example, by differential scanning calorimetry (DSC) at a temperature rise rate of 10° C. / min, and can be taken as the endothermic peak temperature upon melting. The glass transition temperature of each LCP is preferably within the range of 150° C. to 250° C. The glass transition temperature can be measured by differential scanning calorimetry (DSC) at a heating rate of 10° C. / min, and can be taken as the endothermic peak temperature during phase transition.

[0059] When the metal clad laminate manufactured by the manufacturing method of the metal clad laminate of the present disclosure is used for a flexible printed circuit board, the thickness of the LCP film is preferably 20 μm or more, more preferably 25 μm or more. The thickness of the LCP film is preferably 200 μm or less, more preferably 100 μm or less. The thickness of the LCP film can be, for example, the average value of thicknesses measured at any 10 points using a digital thickness gauge.

[0060] When the metal clad laminate manufactured by the manufacturing method of the metal clad laminate of the present disclosure is used for a rigid printed circuit board, a thicker LCP film can be used for the purpose of advantageously exhibiting high frequency characteristics. The manufacturing method of the metal clad laminate of the present disclosure can be applied even to a thick LCP film. For example, even if the thickness of the LCP film is 500 μm to 1,000 μm, the manufacturing method of the metal clad laminate of the present disclosure can be stably applied. In addition, in order to improve the thickness accuracy and tensile strength and further improve the dimensional stability, a rigid printed circuit board can be made by sandwiching a glass cloth between two LCP films. As the glass cloth, a commercially available product having a thickness of 40 μm to 200 μm can be used.

[0061] The first metal foil and the second metal foil may be made of the same material or different materials, but it is preferable that the first metal foil and the second metal foil are made of the same material.

[0062] The material of the metal foil of the present disclosure is not particularly limited, and examples thereof include copper, gold, silver, nickel, aluminum, and stainless steel. From the viewpoints of conductivity, ease of handling, and cost, it is preferable to use copper foil or stainless steel (registered trademark) foil as the metal foil. In addition, as the copper foil, one manufactured by a rolling method (rolled copper foil) or one manufactured by an electrolytic method (electrolytic copper foil) can be used.

[0063] The metal foil may be subjected to a chemical treatment such as acid washing, which is usually applied to copper foil. The thickness of the metal foil is preferably 3 μm to 40 μm, more preferably 10 μm to 20 μm. If the thickness of the metal foil is too thin, the metal foil may be deformed, such as wrinkled, during the manufacturing process of the metal clad laminate. If the thickness of the metal foil is too thick, for example, when used as a flexible wiring board, the bending performance may be reduced.

[0064] The surface roughness of the metal foil in contact with the LCP film is small (i.e., low roughness), and the ten-point mean roughness Rzjis is preferably 1.5 μm or less, more preferably 0.1 μm or more and 1.5 μm or less. Even when the metal foil has such a low roughness, the metal clad laminate of the present disclosure is manufactured by a specific manufacturing method, and therefore the adhesion strength can be improved and the occurrence of blisters can be suppressed. Furthermore, when the ten-point mean roughness Rzjis is, for example, 0.1 μm or less, it becomes difficult to stably ensure the adhesive force. When the ten-point mean roughness Rzjis exceeds 1.5 μm, it becomes difficult to exhibit good high-frequency characteristics. In particular, from the perspective of the balance between high-frequency characteristics and adhesion strength, it is more preferably in the range of 0.1 μm or more and 1.2 μm or less, and more preferably in the range of 0.3 μm or more and 1.0 μm or less.

[0065] The ten-point average roughness Rzjis can be measured by a method in accordance with JIS B0601.

[0066] In order to obtain good high frequency characteristics, it is preferable that the thickness of the metal foil and its surface roughness have a certain relationship. For example, the ratio of the thickness of the metal foil to the ten-point average roughness (unit: μm) is preferably (metal foil thickness) / (ten-point average roughness)=400 / 1 to 30 / 1, and more preferably 200 / 1 to 40 / 1.

[0067] The laminate precursors 10, 20 may be produced using a mold described below.

[0068] The method for producing a metal clad laminate of the present disclosure includes a heating step of heating the laminate precursor after the lamination step at a temperature 15°C to 45°C higher than the higher melting point of the first liquid crystal polymer film and the second liquid crystal polymer film for 1 minute to 60 minutes in an environment with a degree of vacuum of 200 hPa or less. The method for producing a metal clad laminate of the present disclosure can be performed using a vacuum laminator.

[0069] The heating temperature is preferably 15°C higher than the highest first melting point among the melting points of the multiple LCP films to be laminated (first melting point + 15°C) or higher, and 20°C higher than the first melting point (first melting point + 20°C) or higher. In addition, the heating temperature is preferably 45°C higher than the first melting point (first melting point + 45°C) or lower, and 40°C higher than the first melting point (first melting point + 40°C) or lower. If the heating temperature is less than 15°C higher than the first melting point, the anisotropy of the orientation (MD / TD) of the LCP laminate film becomes large. In addition, the adhesive strength between the LCP film and the metal foil becomes low. In addition, the difference between the linear expansion coefficients of MD and TD becomes large. Furthermore, voids are generated in the LCP laminate film, which reduces the resin strength and makes the metal clad laminate more likely to warp. On the other hand, if the heating temperature exceeds a temperature 45°C higher than the first melting point, it becomes difficult to control the orientation of the LCP laminate film. In addition, wrinkles occur in the metal clad laminate, making it difficult to control the thickness. The MD and TD mentioned here are directions based on one of the LCP films to be laminated.

[0070] The temperature rise rate is preferably 1° C. / min to 50° C. / min, more preferably 2° C. / min to 20° C. / min, and even more preferably 5° C. / min to 15° C. / min.

[0071] The heating time in the above heating temperature range is 1 minute or more, preferably 2 minutes or more, and more preferably 5 minutes or more. The heating time in the above heating temperature range is 60 minutes or less, preferably 30 minutes or less, and more preferably 20 minutes or less. If the heating time is short, the anisotropy of the orientation increases. The adhesive strength between the LCP film and the metal foil decreases. The resin strength of the LCP laminate film also decreases. On the other hand, if the heating time is long, the molecular weight increases, causing changes in viscosity and further changes in mechanical properties.

[0072] The heating temperature can be considered to be equal to the set temperature of the heater in contact with the mirror plate surface sandwiching the laminate precursor. The heater is not particularly limited as long as it can heat the laminate precursor. For example, an oil heater, an electric heater, a thin planar heater, etc. can be used as the heater.

[0073] The heating step is performed in an environment with a degree of vacuum of 200 hPa or less. That is, the degree of vacuum in a press machine that pressurizes the laminate precursor is 200 hPa or less. The degree of vacuum is preferably 100 hPa or less, more preferably 50 hPa or less, and even more preferably 20 hPa or less. The degree of vacuum can be 0.1 hPa or more. If the degree of vacuum is higher than 200 hPa, voids will occur in the LCP laminate film, and the resin strength of the LCP laminate film will be easily reduced. The pressure reduction can be performed simultaneously with heating. The pressure reduction is preferably started at a temperature 20°C lower than the first melting point (first melting point -20°C) or lower.

[0074] The method for producing a metal clad laminate of the present disclosure includes a pressurizing step of starting cooling after the heating step, and pressurizing the laminate precursor in the lamination direction at a first pressure of 0.5 MPa to 5 MPa. It is preferable that the laminate precursor is pressed by applying pressure (pressing) to the entire surface of the laminate precursor.

[0075] The first pressure applied to the laminated precursor in the lamination direction is 0.5 MPa or more, preferably 1 MPa or more. The pressure applied to the laminated precursor is 5 MPa or less, preferably 3 MPa or less. If the timing of pressurization is too late or the pressure is too low, the anisotropy of the orientation increases, the adhesive strength of the metal foil decreases, and voids occur in the LCP laminate film, decreasing the resin strength of the LCP laminate film. If the timing of pressurization start is too early or the pressure is too high, the anisotropy of the orientation increases, wrinkles occur in the LCP laminate film, and unevenness occurs in the thickness of the LCP laminate film.

[0076] The pressurizing step is preferably performed while molding the laminate precursor in a mold for molding the metal clad laminate. Figures 4 and 5 show schematic cross-sectional views of the laminate precursor and the mold in the pressurizing step. The embodiments shown in Figures 4 and 5 are merely illustrative, and the shapes of the laminate precursor and the mold are not limited to the dimensional ratios shown in Figures 4 and 5. Although the laminate precursor 20 is shown in Figures 4 and 5, the laminate precursor 10 can also be applied. Furthermore, the laminate precursor may have a multilayer structure as shown in Figures 6 and 7.

[0077] In the embodiment shown in FIG. 4, the laminate precursor 20 is formed in a recess 32a of a lower die 32. The dimension in the planar direction of the recess 32a is preferably adapted to the dimension of the desired metal clad laminate. The dimension in the thickness direction (depth) of the recess 32a is preferably adapted to the thickness of the desired metal clad laminate. When the laminate precursor 20 is pressed by the upper die 31, the recess 32a preferably has a depth such that the upper surface of the second metal foil 4 of the laminate precursor 20 and the upper surface of the lower die 32 are flush with each other under a predetermined pressure applied to the laminate precursor 20.

[0078] In the embodiment shown in Fig. 5, the depth of the recess 34a of the lower die 34 is equal to or greater than the thickness of the desired metal clad laminate. The upper die 33 presses the laminate precursor 20 and has a protrusion 33a that fits into the recess 34a. When the laminate precursor 20 is pressed by the upper die 33, it is preferable that the protrusion 33a fits into the recess 34a in a state in which a predetermined pressure is applied to the laminate precursor 20 by the protrusion 33a. The embodiment shown in Fig. 5 is similar to the embodiment shown in Fig. 4 except for the above.

[0079] The laminate precursor 20 is heated to the melting points of the LCP films 1 and 2 or higher in the heating step. This increases the fluidity of the molten LCP film, making the thickness more susceptible to variation due to pressure. Thus, by using a mold having a recess for forming the metal clad laminate into the final dimensions (shape) of the metal clad laminate to be manufactured, thickness control is facilitated, and a metal clad laminate having a desired thickness can be manufactured.

[0080] The pressurizing step can fuse the LCP films together and bond the LCP film to the metal foil, and can also increase the flatness of the metal clad laminate (reduce the amount of warping) and control the thickness of the metal clad laminate.

[0081] The manufacturing method of the metal clad laminate of the present disclosure includes an annealing step in which the first pressure is reduced to a second pressure, which is 1 / 2 to 1 / 20 of the first pressure, within a temperature range of the lower first glass transition temperature to the first melting point of the glass transition temperatures of the first liquid crystal polymer film and the second liquid crystal polymer film, and the temperature range and the second pressure are maintained for 5 to 60 minutes. By performing the annealing step, the distortion caused by the first pressure in the pressurizing step can be alleviated. That is, the first pressure in the pressurizing step causes distortion in the thickness direction of the laminate precursor, and the distortion is alleviated by reducing the first pressure to the second pressure in the annealing step. As a result, an increase in the linear expansion coefficient in the thickness direction (z direction) of the LCP laminate film can be suppressed. The heating temperature in the annealing step is preferably 5° C. to 40° C. lower than the first melting point, and more preferably 10° C. to 30° C. lower than the first melting point.

[0082] The second pressure is a pressure lowered to within a range of 1 / 2 to 1 / 20 of the first pressure. For example, when the first pressure is 1 MPa, the second pressure is set to 0.05 MPa to 0.5 MPa. The annealing step can reduce the distortion in the thickness direction caused in the laminate by the pressing step. The second pressure is preferably lowered to within a range of 1 / 2 to 1 / 10 of the first pressure, and more preferably within a range of 1 / 2 to 1 / 5. It is more preferable to maintain the temperature range and the second pressure state for 10 to 50 minutes, and even more preferable to maintain the state for 20 to 40 minutes.

[0083] After the annealing step is completed, the material is cooled to room temperature (25° C.) at a rate of 5° C. / min, and the pressure inside the high-temperature press is returned to atmospheric pressure, thereby producing a metal clad laminate.

[0084] In the manufacturing method of the metal clad laminate disclosed herein, by using (1) a laminate precursor having two or more first laminate units in which a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil are laminated in this order, and a thin sheet heater is disposed between adjacent first laminate units and first laminate units, or (2) a laminate precursor having two or more second laminate units in which a second metal foil, a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil are laminated in this order, and a thin sheet heater is disposed between adjacent second laminate units and second laminate units, it is possible to achieve a significant improvement in productivity without unevenness in the heating temperature.

[0085] As shown in FIG. 6, the laminate precursor 30 has two or more first laminate units 7 in which a second liquid crystal polymer film 2, a first liquid crystal polymer film 1, and a first metal foil 3 are laminated in this order, and a thin planar heater 5 is disposed between adjacent first laminate units 7. This prevents unevenness in the heating temperature and greatly improves productivity. The number of layers in the first laminate unit 7 is preferably 2 to 100, more preferably 5 to 50, and even more preferably 5 to 20. In addition, 50 in FIG. 6 is a hot platen of a high-temperature press. A mirror plate may be provided between the first metal foil 3 and the thin planar heater 5.

[0086] As shown in FIG. 7, the laminate precursor 40 has two or more second laminate units 8 in which a second metal foil 4, a second liquid crystal polymer film 2, a first liquid crystal polymer film 1, and a first metal foil 3 are laminated in this order, and a thin planar heater 5 is disposed between adjacent second laminate units 8. This makes it possible to achieve a significant improvement in productivity without unevenness in the heating temperature. The number of layers of the second laminate unit 8 is preferably 2 to 100, more preferably 5 to 50, and even more preferably 5 to 20. In addition, 50 in FIG. 7 is a hot platen of a high-temperature press. In addition, a mirror plate may be provided between the first metal foil 3 and the thin planar heater 5, and between the second metal foil 4 and the thin planar heater 5.

[0087] It is preferable that the thin planar heater 5 is capable of being heated to 300° C. or higher (preferably 300° C. to 600° C.). The thickness of the thin sheet heater 5 is preferably 3,000 μm or less, and more preferably 50 μm or more and 3,000 μm or less. Examples of the thin sheet heater 5 include a mica-coated sheet heater and a silicone-coated sheet heater. The thin sheet heater 5 can be used repeatedly.

[0088] 6 and 7, the lamination precursor 30 and the lamination precursor 40 having the multilayer structure are used, and two or more lamination units are laminated and manufactured by carrying out the heating step, the pressurizing step, and the annealing step similar to the manufacturing method of the metal clad laminate according to the first embodiment of the present disclosure. Then, each lamination unit is taken out of the mold to obtain a metal clad laminate.

[0089] According to the manufacturing method of a metal clad laminate of the present disclosure, it is possible to manufacture a metal clad laminate having an LCP laminate film with improved anisotropy.

[0090] According to the method for producing a metal clad laminate of the present disclosure, the step of improving the anisotropy and the step of bonding a metal foil to an LCP laminate film can be carried out simultaneously, thereby improving production efficiency.

[0091] The metal clad laminate manufactured by the manufacturing method of the metal clad laminate of the present disclosure has high strength and can produce a metal clad laminate having high dimensional accuracy. In addition, even if the roughness of the metal foil is reduced, the LCP laminate film and the metal foil can be bonded with high strength. Since the roughness of the metal foil can be reduced, the transmission loss can be suppressed.

[0092] A metal clad laminate according to a second embodiment of the present disclosure will be described.

[0093] The metal clad laminate according to the second embodiment of the present disclosure is manufactured by the manufacturing method for the metal clad laminate according to the first embodiment of the present disclosure.

[0094] There are cases where it is impossible or simply impractical to directly identify the metal clad laminate of the present disclosure by its composition, structure, properties, etc. In such cases, it should be permitted to identify the metal clad laminate of the present disclosure by its manufacturing method.

[0095] For the liquid crystal polymer film, the LCP laminate film, and the metal foil, the explanation for the metal clad laminate according to the first embodiment is cited.

[0096] As shown in FIG. 8, a metal clad laminate 110 of the present disclosure has a second liquid crystal polymer (LCP) layer 102, a first liquid crystal polymer (LCP) layer 101, and a first metal layer 103 in this order. The peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m; The orientation (MD / TD ratio) of the LCP laminate film consisting of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, the resin strength of the LCP laminate film is 100 MPa or more, and the warpage is 3 mm or less. Area of ​​the LCP laminate film: 10 cm 2 It is preferable that the average number of voids having a diameter of 0.5 mm or less per unit area is 5 or less. It is preferable that the ratio of linear expansion coefficients in the plane direction (MD / TD) of the LCP laminate film is 1.2 or less, and the linear expansion coefficient in the thickness direction (z direction) is 45 ppm or less.

[0097] As shown in FIG. 9, the metal clad laminate 120 of the present disclosure has a second metal layer 104, a second liquid crystal polymer (LCP) layer 102, a first liquid crystal polymer (LCP) layer 101, and a first metal layer 103, in that order. The peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m; The peel strength between the second liquid crystal polymer layer and the second metal layer is 0.9 kN / m to 2.5 kN / m; The orientation (MD / TD ratio) of the LCP laminate film consisting of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, the resin strength of the LCP laminate film is 100 MPa or more, and the warpage is 3 mm or less. Area of ​​the LCP laminate film: 10 cm 2 It is preferable that the average number of voids having a diameter of 0.5 mm or less per unit area is 5 or less. It is preferable that the ratio of linear expansion coefficients in the plane direction (MD / TD) of the LCP laminate film is 1.2 or less, and the linear expansion coefficient in the thickness direction (z direction) is 45 ppm or less.

[0098] The first metal layer and the second metal layer are preferably electrolytic copper layers or rolled copper layers having a thickness of 3 μm to 40 μm.

[0099] In the metal clad laminate according to the second embodiment, the peel strength between the LCP laminate film and the metal foil can be 0.9 kN / m to 2.5 kN / m. The peel strength is preferably 1.0 kN / m to 2.0 kN / m. The peel strength can be measured for a test piece having a length of 50 mm and a width of 10 mm by peeling the metal foil from the LCP laminate film from the end of the short side at a peel speed of 50 mm / min and a peel angle of 90° according to the method specified in JIS K6854-1.

[0100] In the metal clad laminate according to the second embodiment, the resin strength of the LCP laminate film from which the metal foil has been removed can be 100 MPa or more. The resin strength is preferably 100 MPa to 400 MPa. The metal foil (copper foil) can be removed with an aqueous ferric chloride solution. The resin strength can be measured by cutting the LCP laminate film into a test piece shape based on JIS K7124-5 and applying a pulling speed of 12.5 mm / min.

[0101] In the metal clad laminate according to the second embodiment, the ratio of the linear expansion coefficient in the plane direction (MD / TD) of the LCP laminate film from which the metal foil has been removed is preferably 1.2 or less, more preferably 0.9 to 1.2, and even more preferably 1.0 to 1.2. The metal foil (copper foil) can be removed with an aqueous ferric chloride solution. The ratio of the linear expansion coefficient in the in-plane direction can be calculated from the ratio of MD to TD by measuring the linear expansion coefficient in MD and TD in the range of 50°C to 150°C at a heating rate of 10°C / min using a tensile mode of thermomechanical analysis (TMA). MD and TD related to the linear expansion coefficient in the in-plane direction indicate the directions based on the LCP laminate film laminated at the top of the laminated LCP films.

[0102] In the metal clad laminate according to the second embodiment, the linear expansion coefficient in the thickness direction (z direction) of the LCP laminate film from which the metal foil has been removed is preferably 45 ppm or less, more preferably 40 ppm or less, and even more preferably 35 ppm or less. The metal foil (copper foil) can be removed with an aqueous ferric chloride solution. The linear expansion coefficient in the thickness direction (z direction) of the LCP laminate film can be measured by thermomechanical analysis (TMA) in compression mode at a temperature rise rate of 10°C / min in the temperature range of 50°C to 150°C.

[0103] In the metal clad laminate according to the second embodiment, it is preferable that the LCP laminate film from which the metal foil has been removed has no voids or wrinkles. The voids and wrinkles can be confirmed by observing the LCP laminate film from which the metal foil has been dissolved and removed using a stereomicroscope or the like. The metal foil (copper foil) can be removed with an aqueous ferric chloride solution. LCP laminate film area 10cm 2 Preferably, the average number of voids having a diameter of 0.5 mm or less per unit area is 5 or less, more preferably 3 or less, and most preferably 0.

[0104] In the metal clad laminate according to the second embodiment, the degree of warping of the metal clad laminate is suppressed. When a 40 mm×40 mm metal clad laminate is placed on a flat glass plate and one corner is pressed, the height (warping amount) of the diagonal corner above the glass plate is 3 mm or less, preferably 2 mm or less, more preferably 1 mm or less, and further preferably 0.1 mm to 1 mm.

[0105] The metal clad laminate of the present disclosure is suitably used for a flexible printed circuit board or a rigid printed circuit board. EXAMPLES

[0106] The metal clad laminate and the manufacturing method thereof according to the present disclosure will be described below using examples. The metal clad laminate and the manufacturing method thereof according to the present disclosure are not limited to the following examples.

[0107] <Melting point and glass transition temperature> The melting point of the LCP film was measured by differential scanning calorimetry (DSC) at a heating rate of 10° C. / min, and was taken as the endothermic peak temperature upon melting. The glass transition temperature of the LCP film was measured by differential scanning calorimetry (DSC) at a heating rate of 10° C. / min, and was taken as the endothermic peak temperature during the phase transition.

[0108] <Ten point average roughness> The ten-point average roughness of the electrolytic copper foil was measured using a contact type surface roughness meter (manufactured by Mitutoyo Corporation, model: SJ-201).

[0109] (Production Example 1) -Preparation of LCP film 1- 27 mol% of 6-hydroxy-2-naphthoic acid, 73 mol% of p-hydroxybenzoic acid, and 102 mol% of acetic anhydride were charged into a reaction vessel equipped with a distillation tube, and the temperature was raised to 170°C over 1 hour under a nitrogen gas atmosphere, and after maintaining at 170°C for 30 minutes, the temperature was raised to 330°C over 7 hours. After further reacting at 330°C for 10 minutes, the pressure was reduced at 330°C. Next, the pressure was reduced to 10 Torr over 1.5 hours, and when a predetermined stirring torque was reached, polycondensation was completed to obtain a thermoplastic liquid crystal polymer 1 (LCP1). The obtained thermoplastic liquid crystal polymer 1 (LCP1) was heated and kneaded at 280°C to 300°C using a twin-screw extruder, and extruded from a T-die with a diameter of 40 mm and a slit spacing of 0.5 mm to obtain a 50 μm thick LCP film 1. The melting point Tm of the LCP film 1 was 282°C, and the glass transition temperature was 230°C.

[0110] (Production Example 2) -Preparation of LCP film 2- Thermoplastic liquid crystal polymer 2 (LCP2) was synthesized and LCP film 2 was produced in the same manner as in Production Example 1, except that 19 mol% of 6-hydroxy-2-naphthoic acid, 81 mol% of p-hydroxybenzoic acid, 1 mol% of terephthalic acid, and 102 mol% of acetic anhydride were charged into a reaction vessel equipped with a distillation tube in Production Example 1. The melting point Tm of LCP film 2 was 310°C, and the glass transition temperature was 200°C.

[0111] (Production Example 3) -Preparation of LCP film 3- Thermoplastic liquid crystal polymer 3 (LCP3) was synthesized and LCP film 3 was produced in the same manner as in Production Example 1, except that 10 mol% of 6-hydroxy-2-naphthoic acid, 65 mol% of p-hydroxybenzoic acid, 10 mol% of terephthalic acid, 15 mol% of 4,4'-dihydroxybiphenyl, and 102 mol% of acetic anhydride were charged into a reaction vessel equipped with a distillation tube. The melting point Tm of LCP film 3 was 325°C, and the glass transition temperature was 230°C.

[0112] (Test Example 1) - Manufacturing of metal clad laminates - An electrolytic copper foil (ten-point average roughness (Rzjis): 0.9 μm) measuring 300 mm in length, 300 mm in width, and 12 μm in thickness was placed as a first metal foil on a 3 mm mirror plate. The surface of the first metal foil having the average roughness was placed facing away from the mirror plate. Next, the LCP film 1 prepared above, having a thickness of 50 μm, a length of 300 mm and a width of 300 mm, was placed on the first metal foil as a first LCP film. Next, the LCP film 1 prepared above, 50 μm thick, 300 mm long and 300 mm wide, was placed on the first LCP film as a second LCP film. The second LCP film was arranged so that the extrusion direction of the first LCP film and the extrusion direction of the second LCP film were at an angle of 90°. Next, an electrolytic copper foil (ten-point average roughness (Rzjis): 0.9 μm) with a length of 300 mm, width of 300 mm, and thickness of 12 μm was placed as a second metal foil on the second LCP film. The surface of the second metal foil having the above average roughness was arranged to face the second LCP film. Next, a 3 mm mirror plate was placed on the second metal foil. This produced a laminate precursor. This laminate precursor was placed between the upper and lower hot plates of a high-temperature press machine capable of reducing pressure.

[0113] The inside of the high-temperature press was depressurized to a vacuum of 10 hPa. In addition, as the depressurization started, the heating temperature of the laminate precursor was raised to 300°C by increasing the temperature at 10°C / min. This was held at 300°C (maximum heating temperature) for 5 minutes (heating step). After the heating step was completed, cooling was started at a rate of 5°C / min, and immediately thereafter, the laminate precursor was pressurized in the lamination direction with a pressure of 1 MPa (pressurizing step). Subsequently, the material was cooled at a rate of 5°C / min, and when the heating temperature reached 270°C, the pressure was reduced to 0.5 MPa and the material was kept in this heated and pressurized state for 30 minutes (annealing step).Then, the material was cooled to room temperature (25°C) at a rate of 5°C / min, and the pressure inside the high-temperature press was returned to atmospheric pressure to produce a metal clad laminate.

[0114] (Test Examples 2 to 20) - Manufacturing of metal clad laminates - Metal clad laminates of Test Examples 2 to 20 were produced in the same manner as in Test Example 1, except that the conditions in Test Example 1 were changed to those shown in Tables 1 to 5. In addition, "during the heating step" in "timing of starting pressurization in the pressurization step" in Test Example 20 means that pressurization starts before the heating step ends. The "heating step" means the process from when the maximum heating temperature is reached to when cooling starts. If pressure is applied "during the heating process", the problem arises that the molten LCP will flow too much due to the pressure applied when the volume of the LCP is at its maximum. Therefore, it is necessary to apply pressure after the "heating process is completed", when cooling has started and the volume of the LCP has started to shrink. Applying pressure before the start of cooling is the same as "during the heating process".

[0115] Next, the orientation of the laminate film (MD / TD ratio), the peel strength of the metal clad laminate, the resin strength of the laminate film, the linear expansion coefficient of the laminate film (MD / TD ratio), the linear expansion coefficient of the laminate film (z direction), voids in the laminate film, wrinkles in the laminate film, warpage of the metal clad laminate, and thickness accuracy of the laminate film were evaluated as follows. The results are shown in Tables 1 to 5. In the following, MD and TD indicate the directions based on the upper second LCP film of the first LCP film and the second LCP film.

[0116] <Orientation (MD / TD ratio)> After removing the copper foil from each metal-clad laminate with an aqueous ferric chloride solution, the LCD laminate film was subjected to measurement of the microwave transmission intensity in the MD and TD of the sample using a microwave cavity resonator (a microwave molecular orientation meter manufactured by Oji Measurement Instruments Co., Ltd.) to determine the orientation (MD / TD ratio).

[0117] <Peel strength> Each metal clad laminate was cut into a test piece of 50 mm length × 10 mm width, and the copper foil was peeled from the LCP laminate film from the short edge according to the method specified in JIS K6854-1, and the peel strength was measured at a peel angle of 90° and a peel speed of 50 mm / min.

[0118] <Resin strength> After removing the copper foil from each metal clad laminate with an aqueous ferric chloride solution, the LCP laminate film having a thickness of 100 μm was cut into a test piece shape according to the method specified in JIS K7124-5, and the resin strength was measured at a tensile speed of 12.5 mm / min.

[0119] <Linear expansion coefficient (MD / TD ratio)> After removing the copper foil from each metal clad laminate with an aqueous ferric chloride solution, the linear expansion coefficients in MD and TD of the 100 μm thick LCP laminate film were measured in the tensile mode of a thermomechanical analyzer (TMA) at a heating rate of 10°C / min in the range of 50°C to 150°C, and the linear expansion coefficient (MD / TD ratio) was calculated.

[0120] [Linear expansion coefficient (z direction)] After removing the copper foil from each metal-clad laminate with an aqueous ferric chloride solution, the linear expansion coefficient in the lamination direction (z direction) of the 100 μm-thick LCP laminate film was measured at a heating rate of 10°C / min in the range of 50°C to 150°C using a thermomechanical analyzer (TMA) in compression mode.

[0121] <Void> After removing the copper foil from each metal clad laminate with an aqueous solution of ferric chloride, a test piece measuring 200 mm in length and 200 mm in width was cut out from the 100 μm-thick LCP laminate film. The surface of the test piece was observed at a magnification of 50 times using a stereomicroscope (MX50, manufactured by Olympus Corporation). 2 The average number of voids per unit area was measured and evaluated based on the following criteria. [Evaluation Criteria] A: The average number of voids with a diameter of 0.5 mm or less is 0 B: Average number of voids with a diameter of 0.5 mm or less is 1 to 5 C: The average number of voids with a diameter of 0.5 mm or less is 6 or more, or the average number of voids with a diameter of more than 0.5 mm is 1 or more.

[0122] <Wrinkles> After removing the copper foil from each metal-clad laminate with an aqueous ferric chloride solution, a test piece 200 mm long x 200 mm wide was cut out from the 100 μm thick LCP laminate film, and the surface of this test piece was observed at 10x magnification using an image taken with a smartphone (i-Phone 12 pro, Apple Inc.), the average number of wrinkles was measured, and the surface was evaluated based on the following evaluation criteria. [Evaluation Criteria] A: 0 wrinkles B: 1-5 wrinkles, 1-3cm long C: 1 to 5 wrinkles 1 to 3 cm long or 1 or more wrinkles over 3 cm long

[0123] <Warpage amount> A test piece 40 m long x 40 mm wide was cut from each metal-clad laminate and placed on a flat glass plate. When one corner of the test piece was pressed, the height of the test piece above the glass plate at the diagonal position (warping amount; mm) was measured with a vernier caliper and evaluated based on the following evaluation criteria. [Evaluation Criteria] A: 0mm or more and 3mm or less B: More than 3mm and less than 8mm C: More than 8mm and less than 12mm D: More than 12mm

[0124] <Thickness precision> After removing the copper foil from each metal clad laminate with an aqueous ferric chloride solution, the thickness of the 100 μm-thick LCP laminate film was measured at 10 points using a digital thickness gauge (manufactured by Mitutoyo Corporation) and the average value was calculated. The thicknesses of the 10 measured points were evaluated as to whether they were within the range of the average value ±10%.

[0125] [Table 1]

[0126] [Table 2]

[0127] [Table 3]

[0128] [Table 4]

[0129] [Table 5]

[0130] The test examples using LCP films 1 and 2, the test examples using LCP films 1 and 3, and the test examples using LCP films 2 and 3 also gave results at the same level as test examples 1 to 12 in Tables 1 to 3.

[0131] From the results of Tables 1 to 5, in Test Examples 1 to 12, metal clad laminates having LCP films with improved anisotropy could be produced while simultaneously improving anisotropy and copper cladding. In the metal clad laminates of Test Examples 1 to 12, the bonding strength between the LCP film and the metal foil could be increased without using the anchor effect of the metal foil. The laminate films in the metal clad laminates of Test Examples 1 to 12 had high resin strength with suppressed generation of voids and wrinkles. In addition, the metal clad laminates of Test Examples 1 to 12 could be produced with high dimensional accuracy. In addition, the metal clad laminates of Test Examples 1 to 12 achieved a small amount of warping of 3 mm or less.

[0132] The metal clad laminate and its manufacturing method of the present disclosure have been described based on the above-mentioned embodiments and examples, but are not limited to the above-mentioned embodiments and examples, and may include various modifications, changes, and improvements to each of the disclosed elements (including elements described in the claims, specification, and drawings) within the scope of the present invention and based on the basic technical idea of ​​the present invention. Furthermore, various combinations, substitutions, and selections of each of the disclosed elements are possible within the scope of the claims of the present invention.

[0133] Further objects, objectives and modes (including modifications) of the present invention will become apparent from the entire disclosure of the present invention including the claims.

[0134] With respect to numerical ranges set forth herein, unless otherwise stated, any numerical value or range falling within the range should be construed as being specifically set forth herein.

[0135] A part or all of the above-described embodiments may be described as, but are not limited to, the following supplementary notes. Each supplementary note may be combined with each claim in the claims. [Appendix 1] A metal clad laminate produced by the method for producing a metal clad laminate according to the present disclosure. [Appendix 2] A metal clad laminate in which a first metal foil and an LCP laminate film are laminated. [Industrial Applicability]

[0136] The method for producing a metal clad laminate according to the present disclosure can be applied to the production of metal clad laminates used in electronic devices that require high frequency characteristics and low dielectric properties, for example. The metal clad laminate of the present disclosure has high bonding strength and resin strength, as well as high dimensional accuracy, little void generation, and little warping, and is therefore suitable for use in, for example, the production of high-quality flexible printed circuit boards or rigid printed circuit boards. [Explanation of symbols]

[0137] 1. First LCP film 2. Second LCP film 3. First Metal Foil 4 Second Metal Foil 5. Thin surface heater 7 First stacking unit 8 Second stacking unit 10 Laminated Precursor 20 Laminated Precursor 30 Laminated Precursor 31,33 Upper mold 32,34 Lower mold 33a Convex 32a, 34a Recess 40 Laminated Precursor 50 heat plate 101 1st LCP layer 102 Second LCP layer 103 First metal layer 104 Second metal layer 110 Metal clad laminate 120 Metal clad laminate

Claims

1. a lamination step of laminating a first liquid crystal polymer film, a second liquid crystal polymer film, and a first metal foil in such a manner that a surface of the first liquid crystal polymer film and a surface of the second liquid crystal polymer film directly face each other; A heating step of heating the laminate precursor for 1 minute to 60 minutes at a temperature 15°C to 45°C higher than the higher first melting point of the melting points of the first liquid crystal polymer film and the second liquid crystal polymer film in an environment with a vacuum degree of 200 hPa or less; a pressurizing step of starting cooling after the heating step is completed, and pressurizing the laminate precursor in a lamination direction at a first pressure of 0.5 MPa to 5 MPa; In the lamination step, the first liquid crystal polymer film and the second liquid crystal polymer film are laminated so that the stretching direction of the first liquid crystal polymer film and the stretching direction of the second liquid crystal polymer film form an angle of 80° to 100°.

2. 2. The method for producing a metal clad laminate according to claim 1, further comprising an annealing step of reducing the first pressure to a second pressure that is 1 / 2 to 1 / 20 of the first pressure within a temperature range of a first glass transition temperature to the first melting point, which is the lower of the glass transition temperatures of the first liquid crystal polymer film and the second liquid crystal polymer film, and maintaining the temperature range and the second pressure for 5 to 60 minutes.

3. 2. The method for producing a metal clad laminate according to claim 1, wherein the melting point of the first liquid crystal polymer film and the melting point of the second liquid crystal polymer film are each 270° C. to 340° C.

4. The method for producing a metal clad laminate according to claim 1 , wherein the first liquid crystal polymer film and the second liquid crystal polymer film have the same material.

5. 2. The method for producing a metal clad laminate according to claim 1, wherein the ten-point average roughness of the surface of said first metal foil facing said first liquid crystal polymer film is 1.5 [mu]m or less.

6. 2. The method for producing a metal clad laminate according to claim 1, wherein the first metal foil is an electrolytic copper foil or a rolled copper foil having a thickness of 3 μm to 40 μm.

7. 2. The method for producing a metal clad laminate according to claim 1, wherein in the produced metal clad laminate, a peel strength between the first liquid crystal polymer film and the first metal foil is 0.9 kN / m to 2.5 kN / m.

8. In the lamination step, the laminate precursor is prepared in a mold, The method for producing a metal clad laminate according to claim 1 , wherein in the pressing step, the laminate precursor is pressed while being molded by the mold.

9. The laminate precursor further comprises a second metal foil, In the lamination step, the first liquid crystal polymer film and the first metal foil are disposed so that their surfaces directly face each other, The method for producing a metal clad laminate according to claim 1 , wherein a surface of the second liquid crystal polymer film and a surface of the second metal foil are disposed so as to directly face each other.

10. The second metal foil is an electrolytic copper foil or a rolled copper foil having a thickness of 3 μm to 40 μm, The method for producing a metal clad laminate according to claim 9 , wherein the ten-point average roughness of the surface of the second metal foil facing the second liquid crystal polymer film is 1.5 μm or less.

11. 10. The method for producing a metal clad laminate according to claim 9, wherein in the produced metal clad laminate, a peel strength between the second liquid crystal polymer film and the second metal foil is 0.9 kN / m to 2.5 kN / m.

12. The laminate precursor has two or more first laminate units each including a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil laminated in this order; The method for producing a metal clad laminate according to claim 1 , further comprising disposing a thin planar heater between adjacent first lamination units.

13. The laminate precursor has two or more second laminate units each having a second metal foil, a second liquid crystal polymer film, a first liquid crystal polymer film, and a first metal foil laminated in this order; The method for producing a metal clad laminate according to claim 9 , further comprising disposing a thin planar heater between the second lamination units adjacent to each other.

14. The method for producing a metal clad laminate according to claim 12, wherein the thin planar heater is capable of heating to a temperature of 300°C or higher.

15. a second liquid crystal polymer layer, a first liquid crystal polymer layer, and a first metal layer, in that order; The peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m; The orientation (MD / TD ratio) of the laminate film composed of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, and the resin strength of the laminate film is 100 MPa or more; A metal clad laminate having an amount of warping of 3 mm or less.

16. a second metal layer, a second liquid crystal polymer layer, a first liquid crystal polymer layer, and a first metal layer, in that order; The peel strength between the first liquid crystal polymer layer and the first metal layer is 0.9 kN / m to 2.5 kN / m; The peel strength between the second liquid crystal polymer layer and the second metal layer is 0.9 kN / m to 2.5 kN / m; The orientation (MD / TD ratio) of the laminate film composed of the first liquid crystal polymer layer and the second liquid crystal polymer layer is 1.0 to 1.2, and the resin strength of the laminate film is 100 MPa or more; A metal clad laminate having an amount of warping of 3 mm or less.

17. The area of ​​the laminate film is 10 cm 2 17. The metal clad laminate according to claim 15 or 16, wherein an average number of voids having a diameter of 0.5 mm or less per unit area is 5 or less.

18. 17. The metal clad laminate according to claim 15 or 16, wherein the laminate film has a ratio of linear expansion coefficients in a plane direction (MD / TD) of 1.2 or less and a linear expansion coefficient in a thickness direction (z direction) of 45 ppm or less.

19. 17. The metal clad laminate according to claim 15, wherein the first metal layer and the second metal layer are electrolytic copper layers or rolled copper layers having a thickness of 3 μm to 40 μm.

20. The metal clad laminate according to claim 15 or 16, which is used for a flexible printed circuit board or a rigid printed circuit board.

Citation Information

Patent Citations

  • Thermoplastic liquid crystalline polymer film laminatable at low temperature

    JP2005105165A

  • Liquid crystal polymer film, and laminate

    JP2022085734A

  • Winding roll of thermocompression bonding laminated film

    JP2023106957A

  • Laminate and method for producing laminate

    JP2024071004A

  • Thermoplastic liquid crystal polymer film, circuit board, and methods respectively for manufacturing said film and said circuit board

    WO2015050080A1